Corporate Social Responsibility Effect On Company Value With Financial Performance As A Mediation Variable In Companies In Food And Beverage, Transportation, Accommodation Sector Listed On Idx 2021-2022 - Saleh Mattaro, Ghifari; Agustin Rusiana Sari (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2024)
Technology can play an important role for a company in opening up new business opportunities and expanding sales coverage. The accounting information system is a process of capturing, storing, processing and communicating information according to professional needs. The use of financial reports alone is not enough to become the basis of information, additional information is needed in determining a strategy to achieve company goals so that many companies are starting to disclose non-financial reports. non-financial reports are one of the important factors in determining which strategy to choose to carry out the objectives that have been set and linked to financial information in designing a performance measurement system. The purpose of this study is to see the effect of Corporate Social Responsibility on Firm Value with Financial Performance as a Moderation Variable. This research for the 2021 and 2022 periods uses secondary data obtained through the company's personal website and the Indonesia Stock Exchange (IDX). The sampling method used was a purposive sample and obtained as many as 39 companies as a sample. Data were analyzed by using PLS SEM software SmartPLS version 4. The research results obtained are that Economic Performance (Profit) has an effect on Firm Value, but Environmental Performance (Planet) and Social Performance (People) has no effect on Firm Value. Financial Performance cannot mediate Economic Performance (Profit), Environmental Performance (Planet), and Social Performance (People) on Firm Value.